RFID Security Techniques, Protocols and System-On-Chip Design - Kitsos, Paris; Zhang, Yan (Springer US : Imprint: Springer, 2008)
RFID Security: Techniques, Protocols and System-on-Chip Design focuses on the security issues in RFID systems, recent advances in RFID security, attacks and solutions, security techniques, and practical hardware implementation of cryptography algorithms. This book includes coverage of fundamentals, security protocols and techniques, and hardware implementations of cryptographic algorithms dedicated to RFID. Features of the book consist of basic concepts, key technologies, and cutting-edge research outcomes of RFID security comprehensive references on state-of-the-art technologies for RFID security illustrative figures for easy reading and understanding of the materials implementations for algorithms in RFID security selected techniques for enhancing RFID security and performance. The book is written for those interested in wireless networks and mobile communications, especially researchers and engineers interested in communications as it relates to RFID Security.